Concordance and Discordance of Sexual Identity, Sexual Experience, and Current Sexual Behavior in 45-Year-Old Men: Results From the German Male Sex-Study. Issue 4 (28th September 2018) - Goethe, Veronika E.; Angerer, Hannes; Dinkel, Andreas; Arsov, Christian; Hadaschik, Boris; Imkamp, Florian; Gschwend, Jürgen E.; Herkommer, Kathleen
Abstract: Introduction: Discordance of various aspects of sexual orientation has been mostly studied in young adults or in small samples of heterosexual men. Studies focusing on concordance and discordance of aspects of sexual orientation in representative samples of middle-aged men including homosexual men are scarce. Aim: To investigate concordant and discordant sexual behavior in 45-year-old German men with a special focus on homosexual identified men. Methods: Data for this cross-sectional study were collected within the German Male Sex-Study. Participants were 45-year-old Caucasian males from the general population. Men self-reported on sexual identity, sexual experience, and current sexual behavior. Associations between sexual identity, experience, and behavior were analyzed using the chi-square test. Main Outcome Measure: Associations of sexual identity with sexual experience and behavior in a community-based sample of men, and discordance of sexual identity and behavior especially in the subgroup of homosexual men. Results: 12, 354 men were included in the study. 95.1% (n = 11.749) self-identified as heterosexual, 3.8% (n = 471) as homosexual, and 1.1% (n = 134) as bisexual. Sexual identity was significantly associated with sexual experience and behavior. 85.5% of all men had recently been sexually active, but prevalence of sexual practices varied. In hetero- and bisexuals, vaginal intercourse was the most common sexual practice, whereas oral sex was the most common in homosexuals. A discordance of sexual identity was especially found in homosexual men: 5.5% of homosexuals only had sexual experiences with women, and 10.3% of homosexuals recently had vaginal intercourse. In this latter subgroup, only one-quarter ever had sexual experience with a man, and three-quarters had only engaged in sexual activity with a woman. Conclusion: Sexual identity is associated with differences in sexual experience and behavior in German middle-aged men. A considerable proportion of homosexual identified men live a heterosexual life.